The strongest gravitational lenses: IV. The order statistics of the largest Einstein radii with cluster mergers - Redlich, Matthias; Waizmann, Jean-Claude; Bartelmann, Matthias (Astronomy and astrophysics, 2014)
Astronomy & Astrophysics (A&A) is an international journal which publishes papers on all aspects of astronomy and astrophysics